2022
DOI: 10.1039/d1tc04748e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid predictions of the colour purity of luminescent organic molecules

Abstract: Designing luminescent organic materials exhibiting narrowband emission is crucial for achieving high resolution and energy efficient organic light emitting diodes (OLEDs), but remains a significant challenge. Herein we establish the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…We note that on moving from O to S and to Se in a particular series, the corresponding geometries gradually become more puckered (see Figure 3), since the van der Waals radius of the chalcogen atoms increases. Such structural strains are known to increase the emission FWHM, as reported by Ahmad et al; 67 however, the molecules shown in Figure 2 are designed by fusing together adjacent phenyl rings, so that their cores are expected to remain rigid. We recall that rigid structures help minimize non-radiative losses associated with skeleton and vibrational motions, which is beneficial to the achievement of narrowband emission and high luminescence quantum yields.…”
Section: Resultsmentioning
confidence: 83%
“…We note that on moving from O to S and to Se in a particular series, the corresponding geometries gradually become more puckered (see Figure 3), since the van der Waals radius of the chalcogen atoms increases. Such structural strains are known to increase the emission FWHM, as reported by Ahmad et al; 67 however, the molecules shown in Figure 2 are designed by fusing together adjacent phenyl rings, so that their cores are expected to remain rigid. We recall that rigid structures help minimize non-radiative losses associated with skeleton and vibrational motions, which is beneficial to the achievement of narrowband emission and high luminescence quantum yields.…”
Section: Resultsmentioning
confidence: 83%
“…As described above, TBPe (Fig. 1a) is a narrowband fluorescent emitter 44 and given the rigidity required in the molecular structure to achieve narrow emission spectra 66 one would expect the LVC model to provide an accurate description of TBPe excited states. In this section we focus on the lowest excited triplet (T 1 ) and singlet (S 1 ) states which both exhibit π → π* excitation localised on the central aromatic moiety of TBPe .…”
Section: Resultsmentioning
confidence: 99%
“…While a large ΔE FC gap would provide sufficient vibrational excess energy to overcome the ΔnormalESym ${{\rm{\Delta E}}^{{\rm{Sym}}} }$ , this effect would only be present at short time delays (∼10 ps) due to vibrational cooling [53] . However, it is noted that a large ΔE FC may also prove detrimental to achieving narrow emission width [54] …”
Section: Resultsmentioning
confidence: 99%